A flexible self-healing Zn3V2O7(OH)2·2H2O-based Zn-ion battery under continuous folding and twisting. Issue 58 (30th June 2022) - Zhu, Yajun; Lin, Xirong; Jin, Xin; Han, Tianli; Zhang, Huigang; Liu, Jinyun
Abstract : A flexible self-healing Zn-ion battery composed of a Zn3 V2 O7 (OH)2 ·2H2 O nanosheet cathode working with a hydrogel electrolyte is developed, which displays a stable performance in different working conditions. Abstract : Engineering flexible and self-healing batteries is significant for wearable electronics. Here, we develop a flexible self-healing Zn-ion battery with a Zn3 V2 O7 (OH)2 ·2H2 O cathode working with a polyvinyl alcohol hydrogel electrolyte. The battery achieves a high capacity and robust structure during switching and self-healing, and keeps a stable potential after cutting/healing several times. After being bent at 30°, 60°, 90°, 120° and 150°, the capacities remain stable, and the battery delivers 78.6 mA h g −1 when repeatedly folding at 90°, displaying the potential for various applications such as foldable cell phones.